Elements of chemistry - Lavoisier, Antoine Laurent (1743-1794).; Faraday, Michael (1791-1867).; Kerr, Robert (1755-1813).; Encyclopædia Britannica, Inc. (Chicago [etc.] : Encyclopaedia Britannica, 1994)
Indeks.
Utwór pierwszy tł. Robert Kerr.
Keywords: Lavoisier, Antoine Laurent -- (1743-1794) -- tłumaczenia angielskie; Chemia -- 18 w; Elektryczność -- 19 w